Swedish soccer coaches` experiences and application of physical training in male elite soccer: A qualitative content analysis study - Larsson, J.; Olsson, M. C.; Bremander, A.; Larsson, I. (Scandinavian Sport Studies Forum, 2021)
In elite soccer, training becomes more systematic and soccer clubs try to optimise their physiological training programs. Previous research has investigated many aspects of soccer, but research into the coaches` own experiences and continuous improvement of physical training is lacking. The aim of this study was to describe the coaches` experiences and their application of physical training in male elite soccer. The design of the study was explorative and based on a qualitative content analysis with an abductive approach based on a custom version of the four-step quality model—the plan-do-check-act (PDCA) cycle. Fifteen elite soccer coaches in Sweden were interviewed. The result showed that physical training in male elite soccer is an ongoing, continuously improving process that contains four different categories: 1) planning, containing gained experiences, teamwork, and lack of resources; 2) executing with different training methods, weekly rotation, and individual training; 3) evaluating containing monitor training load and physiological testing, and 4) improving with search for knowledge and long-term development. The coaches try to absorb new knowledge and continuously improve their training methods, although lack of resources sometimes does not allow them to introduce new training methods.us.